Serum microRNA‐122 kinetics in patients with chronic hepatitis C virus infection during antiviral therapy. Issue 8 (18th February 2013) - Köberle, V.; Waidmann, O.; Kronenberger, B.; Andrei, A.; Susser, S.; Füller, C.; Perner, D.; Zeuzem, S.; Sarrazin, C.; Piiper, A.
Summary The levels of the liver‐specific microRNA‐122 (miR‐122) circulating extracellularly in the blood have been shown to be increased upon liver damage. However, it is unknown if the levels of serum miR‐122 are altered during antiviral therapy and reflect the therapeutic success. Here, we investigated miR‐122 serum levels in patients with chronic hepatitis C virus (HCV) genotype 1 infection during antiviral therapy with pegylated interferon and ribavirin. Therefore, sera from 60 patients with chronic HCV infection genotype 1 showing sustained virological response (SVR), non‐response or relapse to therapy obtained at baseline, 4, 12, 24 weeks, end of treatment and follow‐up were analysed retrospectively for miR‐122 content by quantitative real‐time reverse transcription PCR. The time courses of miR‐122 were correlated with HCV RNA as well as standard liver parameters. We found that while there was no relation between serum miR‐122 and HCV RNA levels at baseline, the decline in HCV RNA upon beginning of the therapy closely correlated with the reduction of serum miR‐122 in the three different patient groups. Moreover, the serum miR‐122 level correlated well with alanine aminotransaminase, a marker of ongoing liver damage. At follow‐up serum miR‐122 levels remained low in SVR, but increased to baseline levels in patients not responding or showing relapse to therapy. In contrast, the serum concentration of the ubiquitously expressed miR‐16 did not change during therapy. We conclude that the serum level of miR‐122 well reflects the success of interferon/ribavirin therapy in patients with chronic HCV infection.